RELICTS OF THE CULT OF NATURE IN THE FAMILY AND HOUSEHOLD RITUALS OF THE KARAKALPAK PEOPLE IN ANCIENT AND IN PRESENT TIME - Kamalova Raushan Sabirovna (Journals Park Publishing, 2022)
The article deals with folk Karakalpak traditions and beliefs in the field of relics of nature. The cultural relationship of the Karakalpak people with other peoples of Central Asia and Kazakhstan in the field of traditional folk cultures is also considered.
Keywords: Republic of Karakalpakstan, Karakalpaks, traditional holidays, rituals, relics of nature, cult of water, cult of plants.